Physical Activity and Gastric Cancer Risk: A Systematic Review and Meta-Analysis. Issue 6 (November 2016) - Psaltopoulou, Theodora; Ntanasis-Stathopoulos, Ioannis; Tzanninis, Ioannis-Georgios; Kantzanou, Maria; Georgiadou, Despoina; Sergentanis, Theodoros N.
Abstract : Objective: Physical activity represents a well-established way to prolong the life span; yet, it remains an unfulfilled goal for a great part of the population. In parallel, the burden of gastric cancer is considerable throughout the globe. In that context, the present meta-analysis aims to shed light on the association between physical activity and gastric cancer risk. Data Sources: Eligible observational studies were sought in PubMed up to June 01, 2015. In addition, a snowball procedure was conducted and contact with authors was implemented. Separate analyses were performed by type of physical activity (total; occupational; recreational), study design, published/provided data, anatomical site, and study location, along with stratification by gender. Main Results: Ten cohort studies (7551 incident cases in a total cohort size of 1 541 208 subjects) and 12 case–control studies (5803 cases and 73 629 controls) were eligible. "Any" type of physical activity was associated with lower risk of gastric cancer [pooled relative risk (RR) = 0.81; 95% CI: 0.73 to 0.89], which was reproducible in men (pooled RR = 0.87; 95% CI: 0.77-0.99). The protective effect was significant in the subgroup analyses of published data, noncardia cancer (pooled RR = 0.62; 95% CI: 0.52-0.75), and studies stemming from Asia (pooled RR = 0.82; 95% CI: 0.74-0.90). Conclusions: This meta-analysis suggests a protective effect of physical activity regarding gastric cancer risk, especially in Asian populations. Abstract : Supplemental Digital Content is Available in the Text.